Long-Term Mortality Following Transvenous Lead Extraction: Data from EXTRACT Registry - Sylwia Gładysz-Wańha; Michał Joniec; Wojciech Wańha; Eugeniusz Piłat; Anna Drzewiecka; Rafał Gardas; Jolanta Biernat; Andrzej Węglarzy; Danuta Łoboda; Joanna Stachańczyk; Krzysztof Stanisław Gołba (Journal of Clinical Medicine, 2026)
Background/Objective: The EXTRACT registry cohort of 504 patients undergoing transvenous lead extraction (TLE) has been previously reported in terms of periprocedural safety and short-term outcomes. Data on long-term mortality and its predictors in this population remain limited. The study aimed to identify risk factors for overall mortality at three years following TLE. Methods: This is a secondary, long-term follow-up analysis of the previously published EXTRACT registry cohort of 504 consecutive patients who underwent TLE between 2016 and 2022. We conducted a univariate analysis to predict mortality risk following TLE, followed by Cox regression with cross-validation to identify independent predictors of mortality over a 3-year follow-up period; Brier score assessed prediction accuracy for mortality; and decision curve analysis evaluated the clinical usefulness of the model. Results: Mortality data were completed for 487 patients at three-year follow-up. Long-term outcomes of TLE showed that patients with CIED infection (p = 0.0091), higher NYHA class (p < 0.0001), arterial hypertension (p = 0.0068), previous stroke (p = 0.0092), upgraded to condition pacing post-TLE (p = 0.0092), and higher CHA2DS2-VA score (p = 0.0026) had markedly higher mortality at three-year follow-up. Increased mortality was independently associated with estimated glomerular filtration rate (eGFR) and the CHA2DS2-VA score. Risk increased incrementally with each 1 mL/min/1.73 m2 decrease in eGFR (hazard ratio, 0.99; 95% CI, 0.98–0.99), and each 1-point increase in CHA2DS2-VA conferred a 12% higher mortality rate (hazard ratio, 1.12; 95% CI, 1.02–1.23). Conclusions: In this prospective registry, 3-year mortality after TLE was driven predominantly by baseline clinical risk rather than procedural factors. Renal dysfunction and a higher CHA2DS2-VA score independently predicted death, supporting the incorporation of kidney function and global vascular risk into pre-extraction assessment and post-extraction management.